Determination and Application of Critical Control Points on Ebi Fry Production (Value Added Product) at PT. Jala Sembilan Semarang, Central Java - Revanda Rizky Putraisya; Juni Triastuti (Universitas Airlangga, 2022)
Java. The quality of ebi fry products is largely determined by the quality management of the company, one of it is the determination and application of the Critical Control Point (CCP). The purpose of this study is to determine the determination of CCP and the problems that occur in the application of CCP in the production of ebi fry at PT. Jala Sembilan Semarang, Central Java. This Field Work Practice is carried out at PT. Jala Sembilan which is located at Jalan Tugu Industri IV No. 3, Randu Garut, Tugu District, Semarang City, Central Java on December 30, 2019 to January 23, 2020. The working method used is a descriptive method with data collection including primary data and secondary data. Data collection can be done by means of active participation, observation, interviews, and literature review. Determination of CCP is done after analyzing the hazards in each production process flow. Ebi fry production at PT. Jala Sembilan has 2 CCPs, namely on package receiving and metal detecting. The application of CCP on the receipt of ebi fry packaging has been carried out by checking allergen labels. The application of CCP in metal detecting has encountered problems, namely the metal detector machine that has interference and is not sensitive so that every time the product is passed the alarm is always on.